Heat recovery in an actual LNG supply chain: Retrofitting of designed heat exchange networks (HENs) for potential fuel saving - Asmaa Othman (10269756) (2021)
The demand for liquefied natural gas (LNG) is steadily increasing and projected to become an important component of global energy demand. Although LNG processing requires high-energy to convert the gas into liquid, it is still the most preferable method of supply due to technical, economic, safety, and political reasons. Energy integration strategies and process optimization between units have been emphasized as ways to reduce energy demand. In this study, a rigorous simulation for proposed heat exchanger networks (HENs) between sulfur recovery units (SRU) and gas sweetening units (GSU) that exhibit heat sources and sinks was conducted. The HENs were designed using pinch analysis tools in Aspen Energy Analyzer (AEA) and were used to determine the maximum energy recovery and potential fuel savings after retrofitting within LNG supply chain. The feasibility of retrofitting the HENs into LNG plant without affecting process conditions or product quality was also determined. Although universal HEN reduces energy consumption of the existing plant by 68%, the network complexity limits its practical application. Simplified HENs between the sub-units reduced energy demand by 50% and achieved fuel saving of 34%. Retrofitting HENs improved existing LNG energy integration, enhanced process economy, reduced fossil fuel burning and protected the environment. Other Information Published in: Chemical Engineering and Processing - Process Intensification License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cep.2021.108477